2022
DOI: 10.1021/acsami.2c09604
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Behavior at Crystalline/Amorphous Interface of Transparent Oxide Semiconductor and Its Effects on Carrier Transport and Crystallization

Abstract: The role of disorder and particularly of the interfacial region between crystalline and amorphous phases of indium oxide in the formation of hydrogen defects with covalent (In–OH) or ionic (In–H–In) bonding are investigated using ab initio molecular dynamics and hybrid density-functional approaches. The results reveal that disorder stabilizes In–H–In defects even in the stoichiometric amorphous oxide and also promotes the formation of deep electron traps adjacent to In–OH defects. Furthermore, below-room-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…From this result, we can identify that the deconvoluted OH peak area significantly deviates from the calculated peak area when the highly crystallized structure collapses and an amorphous matrix appears, which corresponds to the negative shift of V th . From this result, we deduce that the almost constant V th until 40 at% of indium and the abrupt increase over it could be related to the facile formation of hydrogen defects along the interface of the crystallites and the amorphous matrix compared to crystalline IZO, and the subsequent increase in the donor state. This also influenced the stability of the device, as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…From this result, we can identify that the deconvoluted OH peak area significantly deviates from the calculated peak area when the highly crystallized structure collapses and an amorphous matrix appears, which corresponds to the negative shift of V th . From this result, we deduce that the almost constant V th until 40 at% of indium and the abrupt increase over it could be related to the facile formation of hydrogen defects along the interface of the crystallites and the amorphous matrix compared to crystalline IZO, and the subsequent increase in the donor state. This also influenced the stability of the device, as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…After thermal annealing at 350 • C, the images showed that the surface morphology of In the sputtering process may be the underlying cause of this phenomenon, as it significantly enhances the films' ability to fix oxygen. It has been mentioned in the literature that as the temperature increases, the unstable interfacial In-H-In defects release hydrogen, which in turn combines with oxygen to form stronger covalent bonds, such as In-OH [32,33]. Furthermore, the O/In ratios of the annealed In2O3 film are observed to be lower than that of the annealed In2O3:H film.…”
Section: Resultsmentioning
confidence: 96%
“…Previous modeling work on GaN crystallization has focused on understanding CVD and molecular beam epitaxy processes, not solidification from the melt. , In addition, there has been no atomic-scale modeling of adatom diffusion on a substrate surface due to the limited force fields capable of modeling both the bulk/melt regions and adequately representing all the different phases and atom-types involved in the process. Even though there has been previous work studying the crystallization of liquid semiconductors and associated energy changes, the system was constrained to bulk phase solidification from liquid to crystal. Therefore, there remains a need to understand the reaction mechanism of additive manufacturing processes for semiconductors with an accurate and transferable force field capable of representing different phases. To do so, we utilize a machine learning-derived transferable force field called FLARE, , that is capable of capturing a reaction-diffusion system and modeling several chemical species and the multiple phases involved in this additive manufacturing process .…”
Section: Introductionmentioning
confidence: 99%